The Tooth Agenesis in Clinical Practice: A review of Case Reports - Michael Dany,; Ameta Primasari,; Ervina Sofyanti,; Sry Suryani Widjaja,; Thantrira Porntaveetus, (Dentika: Dental Journal, 2025)
Tooth agenesis (TA) relates to multiple congenital dental disorder and the most prevalent developmental disorders affecting approximately 200 million people globally. The management of TA require interdisciplinary dental approaches. Therefore, this study aimed to conduct a case report evaluation of TA based on population and ethnicity. This scoping reviews based on Preferred Reporting Items for Systematic Reviews and Meta-Analyses, has been registered in Open Science Framework. Relevant articles were retrieved from Proquest, Science Direct, PubMed, and SpringerLink databases with keywords comprising of ‘Prevalence’ AND ‘Tooth Agenesis’ AND ‘Nonsyndromic or Syndromic’. From 2014 to 2024, there were only five non-syndromic tooth agenesis case reports were included to be reviewed. The review of multiple case reports of tooth agenesis demonstrated significant variability in clinical and radiography evaluation involving inheritance pattern. By early identification in mixed dentition, the comprehensive and individualized treatment approaches are required to address both esthetics and functional outcomes. Further population-based studies of genetic involvement in TA can contribute early detection of malocclusion.